Studentsâ Perception on Ideal Age of Marriage and Childbearing - Subranmiam, Mohanambehai; Mutyara, Kuswandewi; Syam, Hanom Husni (Althea Medical Journal, 2015)
Background: Early-age marriage is still common in Indonesia, especially in the rural areas. There are manyÂ negative effects of the marriage; the young brides may get lower education, lower social status, minimumÂ reproduction control, higher maternal mortality, higher domestic violence rate and others. Thus, this studyÂ is conducted to identify the studentsâ perception on the ideal age of marriage and childbearing.Methods: A cross-sectional descriptive study was conducted from June to September 2013 in JatinangorÂ using secondary data from Jatinangor Cohort Survey Team. The data comprised two hundred and twentyÂ students from Jatinangor Senior High School and PGRI Vocational School. A hundred and ten males and aÂ hundred and ten females were chosen by random sampling. Questionnaires were given after the writtenÂ informed consent was obtained from the students.Results: The results showed 74.55% of the students chose 19Â¬â24 years old as the ideal age of marriage forÂ a woman and 68.64% students chose 25â30 years old as the ideal age of marriage for a man. Moreover, forchildbearing, 25â30 years old was chosen to be the ideal age for both man and woman. The percentage ofÂ students agreed to this was 74.55% and 54.09% respectively.Conclusions: Majority of the students agreed on 19â24 years old and 25â30 years old as the ideal age ofÂ marriage for woman and man respectively. For childbearing, 25â30 years old was concluded as the ideal agefor both genders. [AMJ.2015;2(4):591â6]Â DOI:Â 10.15850/amj.v2n4.661